National Forest Policy and Raw Material Supplies for Wood Based Industries in India - Lal, Piare (Indian Forester, 2000)
Intense biotic pressures and major weaknesses in the National Forest Policy and its implementation have resulted in serious degradation of forest resources. The gap between supply and sustainable availability of biomass including fodder, fuel wood, industrial round timber and NTFP is growing. Unfortunately, the revised National Forest Policy announced in 1988 has not been conducive to sustainable development of forest based raw materials and wood based industries. Substantial improvement in productivity of forest resources on sustainable basis is critically important for meeting the national needs and conserving the forest resources. Innovative policy initiatives are required for reforestation of 32 million ha degraded forest areas in a time bound manner with appropriate species matching the present site conditions. Priority for reforestation should be given for areas with good soils but devoid of tree cover as it is counter productive to tackle most difficult sites first meanwhile allowing the better sites to degrade to the point of no return. As massive financial investments will be required for reforestation of degraded forest lands supplemented with genetically improved planting stock and competent professional management with accountability for results, corporate sector and all sections of society should be encouraged to participate in the national effort of reforestation. Simultaneously Policy must promote farm forestry and afforestation of wastelands and marginal agricultural lands, through innovative policy changes, fiscal incentives and tax benefits.